Peran Green Chemistry dalam Mewujudkan Pembelajaran Kimia yang Bermakna: Kajian Literatur - Nyoman Sriastuti; Astin Lukum; Masrid Pikoli (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
Green chemistry is a relevant approach in supporting meaningful and sustainability-oriented chemistry learning. This study aims to (1) analyze the implementation and integration of green chemistry principles in chemistry learning, (2) analyze its role in realizing meaningful learning, (3) analyze its impact on students’ conceptual understanding and environmental awareness attitudes, and (4) analyze the challenges and opportunities of its implementation. This research uses a qualitative approach with a literature review design of accredited national journal articles and reputable international journals from the 2020–2026 period. Out of 40 identified articles, 24 articles were analyzed using thematic analysis. The results show that (1) the implementation of green chemistry is carried out through active learning, development of instructional materials, utilization of technology, and contextual approaches; (2) green chemistry plays a role in realizing meaningful learning by connecting concepts to environmental issues; (3) its integration has a positive impact on students’ conceptual understanding and environmental awareness attitudes, although the level of improvement is generally moderate; and (4) its implementation still faces challenges related to teacher competence, learning resources, and curriculum support, but it also has opportunities for further development. The conclusion of this study is that green chemistry plays a strategic role in realizing meaningful chemistry learning by linking chemical concepts to real environmental problems and supporting sustainable chemistry education.